Alonso Zamora Vicente, lembranza del ventanal a la calle de un aula gallega (1916-2006). Alonso Zamora Vicente, lembranza of the large windou from a Galician room to the Street (1916-2006) - González Martel, Juan Manuel (Madrygal. Revista de Estudios Gallegos, 2006)
Sin resumen